1994
DOI: 10.1046/j.1471-4159.1994.62020739.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neurofilament Protein NF‐L and NF‐H Immunoreactivity Following Kainic Acid‐Induced Seizures

Abstract: Postlesion plasticity of neuronal processes might contribute to secondary spontaneous seizures after kainic acid administration . In this study, neurofilament (NF) proteins were examined following intraperitoneal injection of kainic acid, and special reference was given to temporal changes in quantity and quality of the NF light (NF-L) and heavy {NF-H) subunits . A pronounced decrease in phosphorylation-related immunoreactivity of NF-H occurred as early as 1 day after the injection in the amygdala/pyriform cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…Again, the phosphorylation state of neurofilament subunits is a major regulatory variable. Following kainic acid-induced lesions, a pronounced dephosphorylation of the neurofilament heavy chain and a decrease in NF-L have been reported [Wang et al, 1994;Vaidya et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the phosphorylation state of neurofilament subunits is a major regulatory variable. Following kainic acid-induced lesions, a pronounced dephosphorylation of the neurofilament heavy chain and a decrease in NF-L have been reported [Wang et al, 1994;Vaidya et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role in the mechanical stabilization of neuronal morphology, it may also be involved in the regulation of plastic changes that neurons may undergo in development or even in the adult brain. The NF-L has been implicated in axonal sprouting in the adult brain [Wang et al, 1994;Vaidya et al, 2000]. A genetically induced NF-L deficiency in mice leads to a decline of other neurofilaments as well; at the same time, levels of tubulin and GAP-43 rise in neurons of such animals [Zhu et al, 1997a].…”
Section: Map-1bmentioning
confidence: 99%
“…Consequently, it has been suggested that the phosphorylation of NF-L could be associated with the induction and/or maintenance of neuronal plasticity during the long term potentiation. In pathological situations, such as ischemia (Nakamura et al, 1992;Kaku et al, 1993), kainic acid-induced seizures (Wang et al, 1994;Yang et al, 1995), and traumatic brain injury (Posmantur et al, 2000), phosphorylation/dephosphorylation is thought to be one early sign of cellular damage, the changes in the dendrites preceding those in the axons (Posmantur et al, 2000). Further studies using several different antibodies, which detects various phosphoepitopes will be needed to clarify the role of phosphorylation in the stability of NF proteins.…”
Section: Lopez-picon Et Almentioning
confidence: 99%
“…NF proteins, in particular NF-M and NF-H, are phosphorylated extensively, with highly conserved phosphorylation sites (Julien and Mushynski, 1983;Carden et al, 1985;Schlaepfer, 1987). It is suggested that the phosphorylation plays an important role in stabilizing and continuously remodeling NF filaments during the axonal growth and might be connected to plasticity of both axons and dendrites (Schlaepfer, 1987;Wang et al, 1994;Hashimoto et al, 2000;Posmantur et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation